2004
DOI: 10.1080/14634980490281353
|View full text |Cite
|
Sign up to set email alerts
|

Influence of habitat, water quality, and land use on macro-invertebrate and fish assemblages of a southeastern coastal plain watershed, USA

Abstract: Most states in the U.S. are currently developing methods for assessing the integrity of aquatic habitats through the development of regional biocriteria. While multimetric indices have been used to show community composition, pollution tolerance, species diversity, and trophic structure with a combined index, the specific environmental factors that drive biological communities may be better explained through the use of multivariate statistical techniques. Macroinvertebrate and fish assemblages were sampled alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 16 publications
2
39
0
Order By: Relevance
“…J. Lim. 47 (2011) S3-S14 S9 are habitat quality and land use intensity (Sawyer et al, 2003;Hering et al, 2006). The macroinvertebrate and fish classes showed a closer relationship with BOD (r= 0.50, 0.43, respectively) than with habitat quality (r= 0.41, 0.32, respectively), confirming the findings of previous studies.…”
Section: Relationships Among Naemp Criteria and Their Implicationssupporting
confidence: 84%
See 1 more Smart Citation
“…J. Lim. 47 (2011) S3-S14 S9 are habitat quality and land use intensity (Sawyer et al, 2003;Hering et al, 2006). The macroinvertebrate and fish classes showed a closer relationship with BOD (r= 0.50, 0.43, respectively) than with habitat quality (r= 0.41, 0.32, respectively), confirming the findings of previous studies.…”
Section: Relationships Among Naemp Criteria and Their Implicationssupporting
confidence: 84%
“…However, these studies show only a large picture of the impacts of human disturbance (i.e., stress) on lotic environments and their resident biological assemblages but cannot explain assemblage-specific responses to stress. Relatively few studies have examined the responses of different assemblages to stress (Paller, 2001;Bryce and Hughes, 2003;Sawyer et al, 2003;Griffith et al, 2005;Hering et al, 2006). Such understanding is critical in watershed management and stream/river restoration for targeting particular assemblages in specific streams/rivers and for building ecological models.…”
Section: Implementation and Conclusionmentioning
confidence: 99%
“…For example, Johnson et al (1997) found that the whole catchments explained slightly less of the water quality variability than that in the 100 m buffer. Similar analysis of land use data by Sawyer et al (2004) showed that agricultural practices and urbanization occurring within 30 m buffer of the stream had higher correlations to biotic community structure than that at the catchments. Conversely, Sliva and Williams (2001) used multiple regressions to show that land use characteristics at the catchment scale had slightly greater influence on water quality than that in the 100 m buffer.…”
Section: Introductionmentioning
confidence: 65%
“…We used correlation coefficient (R 2 ) in the stepwise regression model as explanatory variable (Sliva and Williams 2001) to address the issue. Using R 2 to compare the relationships at catchments scale vs. buffers scale allowed us to determine whether land use near water body is a better predictor of water quality than that over the entire catchments (Hunsaker and Levine 1995;Johnson et al 1997;Sliva and Williams 2001;Sawyer et al 2004).…”
Section: Evaluation Of Correlation Between Land Use and Water Qualitymentioning
confidence: 99%
“…Refinement of the indices would require assessment and macroinvertebrate sampling of a full range of stream conditions including high-quality reference and impaired streams in addition to restored streams. In addition, consideration should be given to adding water chemistry, flow and sampling season, as all of these factors have relevance to macroinvertebrate metrics [51][52][53][54]. The SPA was applied to 156 restored and un-restored streams between 2006 and 2012 [27].…”
Section: Discussionmentioning
confidence: 99%